Socio-economic structure and crisis of peripheral capitalism - Raúl Prebisch (CEPAL Review, 1978)
In the present article the author continues and expands the critical analysis of peripheral capitalism which he began in another that was published in the first issue of this Review. His central contention is that in peripheral societies the development process — whereby the accumulation of capital in the form of goods and training of human resources makes it possible to step up the productivity of the labour force and thus to increase the total product— is not carried out with the necessary efficiency at the social and even, in many cases, at the economic level.